Genetic parameters and seasonal response of pod and yield traits in ten Indonesian winged bean (Psophocarpus tetragonolobus) lines - RETNO DWI ANDAYANI; IZMI YULIANAH; DARMAWAN SAPTADI; KUSWANTO KUSWANTO (Society for Indonesian Biodiversity, 2026)
Abstract. Andayani RD, Yulianah I, Saptadi D, Kuswanto. 2026. Genetic parameters and seasonal response of pod and yield traits in ten Indonesian winged bean (Psophocarpus tetragonolobus) lines. Biodiversitas 27 (8): d270811. https://doi.org/10.13057/biodiv/d270811. Winged bean (Psophocarpus tetragonolobus) is an underutilized tropical legume with wide phenotypic diversity in Indonesia, but information on genetic parameters and seasonal responses remains limited. This study aimed to evaluate phenotypic variation, estimate genetic parameters, assess line × season interaction, and identify promising Indonesian winged bean lines for pod and seed yield across two planting seasons. Ten lines were evaluated during the dry (May-October 2023) and wet seasons (November 2023-April 2024) at Kediri, East Java, Indonesia, using a randomized complete block design with three replications per season. Phenology, pod, and yield traits were analyzed using combined ANOVA, and genetic parameters were estimated across seasons. Season, genotype, and their interaction significantly influenced several key traits, indicating differential responses to environmental conditions. The dry season generally enhanced productivity, producing longer pods, heavier fresh pods, and higher pod and seed yields than the wet season. Fresh pod yield increased from 2.36 to 3.76 kg per plant, while fresh pod weight increased from 33.42 to 42.16 g per pod. High broad-sense heritability for pod length (0.94), fresh pod weight (0.95), fresh pod yield (0.86), and seed yield (0.94) indicated strong genetic control and good selection potential. Path analysis identified fresh pod weight, pod length, and pod number as major determinants of yield. Principal component and cluster analyses further distinguished superior genotypes based on productivity and trait characteristics. NSM2 showed the highest fresh pod yield (4.57 kg per plant) and seed yield (488.01 g per plant), with stable performance across seasons. These findings demonstrate substantial seasonal effects on winged bean productivity and identify NSM2 as a promising candidate for breeding high-yielding, environmentally resilient cultivars.